Treatment of late paravalvular regurgitation after transcatheter aortic valve implantation: prognostic implications. (22nd March 2023) - Landes, Uri; Hochstadt, Aviram; Manevich, Lisa; Webb, John G; Sathananthan, Janarthanan; Sievert, Horst; Piayda, Kerstin; Leon, Martin B; Nazif, Tamim M; Blusztein, David; Hildick-Smith, David; Pavitt, Chris; et al.
Abstract: Aims: Paravalvular regurgitation (PVR) after transcatheter aortic valve implantation (TAVI) is associated with increased morbidity and mortality. The effect of transcatheter interventions to treat PVR after the index TAVI was investigated. Methods and results: A registry of consecutive patients who underwent transcatheter intervention for ≥ moderate PVR after the index TAVI at 22 centers. The principal outcomes were residual aortic regurgitation (AR) and mortality at 1 year after PVR treatment. A total of 201 patients were identified: 87 (43%) underwent redo-TAVI, 79 (39%) plug closure, and 35 (18%) balloon valvuloplasty. Median TAVI-to-re-intervention time was 207 (35; 765) days. The failed valve was self-expanding in 129 (63.9%) patients. The most frequent devices utilized were a Sapien 3 valve for redo-TAVI (55, 64%), an AVP II as plug (33, 42%), and a True balloon for valvuloplasty (20, 56%). At 30 days, AR ≥ moderate persisted in 33 (17.4%) patients: 8 (9.9%) after redo-TAVI, 18 (25.9%) after plug, and 7 (21.9%) after valvuloplasty ( P = 0.036). Overall mortality was 10 (5.0%) at 30 days and 29 (14.4%) at 1 year: 0, 8 (10.1%), and 2 (5.7%) at 30 days ( P = 0.010) and 11 (12.6%), 14 (17.7%), and 4 (11.4%) at 1 year ( P = 0.418), after redo-TAVI, plug, and valvuloplasty, respectively. Regardless of treatment strategy, patients in whom AR was reduced to ≤ mild had lower mortality at 1 year compared with those with AR persisting ≥ moderate [11 (8.0%) vs. 6 (21.4%); P = 0.007]. Conclusion: This study describes the efficacy of transcatheter treatments for PVR after TAVI. Patients in whom PVR was successfully reduced had better prognosis. The selection of patients and the optimal PVR treatment modality require further investigation. Structured Graphical Abstract: Structured Graphical Abstract Transcatheter treatment of paravalvular regurgitation (PVR) after transcatheter aortic valve implantation (TAVI) using redo-TAVI, plug closure, or balloon valvuloplasty. Out of 201 patients, the failed valve was self-expanding in two-thirds and balloon-expandable in one-third of the patients. There were 87 patients (43%) who underwent redo-TAVI, 79 (39%) plug closure, and 35 (18%) balloon valvuloplasty. At 30 days, aortic regurgitation (AR) ≥ moderate persisted in 33 (17.4%): 8 (9.9%) after redo-TAVI, 18 (25.9%) after plug closure, and 7 (21.9%) after valvuloplasty ( P = 0.036). Regardless of treatment strategy, patients with persistent AR ≥ moderate had higher 1-year mortality compared with those in whom AR was reduced to ≤ mild.